IN VITRO ELIMINATION OF DAHLIA MOSAIC VIRUS BY USING MERISTEM CULTURE, ELECTROTHERAPY AND CHEMOTHERAPY - & et al., Nerway (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was conducted to investigate the effect of different in vitro techniques on elimination of dahlia mosaic virus. Meristems of Dahlia mosaic virus (DMV) infected dahlias, with 0.2-0.3 mm in length, were cultured on Murashige and Skoog (MS) medium. Based on DAS-ELISA, 100% of the survived plantlets by meristem culture were virus-free. DMV infected stem segments with two axillary buds were treated at three different levels of electric currents (15, 25 and 35 mA) and two time courses (10 and 20 min) in an electrophoresis tank and cultured on MS medium. The treatment of 35 mA for 20 min was the best for viral elimination from diseased dahlias by 85% followed by 25 mA for 20 min by 70%. Acyclovir and salicylic acid were the antivirals were used to eliminate DMV from the infected dahlias. For chemotherapy, nodes were cultured on MS media supplemented with antivirals at 0, 10, 20, 30, 40 and 50 mg/l for 20 and 30 days. The highest concentration of acyclovir (50 mg/l) for 30 days were the best treatments as its highest effectiveness on elimination ability (90.67%) but gave only 49% for plantlet survival. Whereas 40 mg/l acyclovir for 30 days gave elimination ability (80%) and plantlet survival (89.67%). The therapy containing salicylic acid at 40 mg/l for 30 days was the best as its highest effectiveness on DMV elimination ability (100%). But the concentration of salicylic acid at 30 mg/l for 30 days was the best treatment (chemotherapy efficiency= 49.21) as well as DMV elimination ability (75.33%) and plant survival (65.33%). The in vitro developed dahlia plantlets were tested for DMV-freeness using DAS-ELISA. The using therapies (electrotherapy and chemotherapy) can play a good role in virus elimination because they need the minimum period of time to regenerate fully developed healthy plants as long as 2-3 months.